Pengendalian Mutu Crude Palm Oil (CPO) Dengan Metode Control Chart dan Failure Mode and Effect Analysis (FMEA) Pada Pabrik Kelapa Sawit PT.XYZ - Rozza Zara Syafira; Sri Haryani Anwar; Zalniati Fonna Rozali (Agricultural Faculty, 2022)
The purpose of this research is to analyze the consistency of daily CPO quality at the palm factory PT. XYZ for the last 3 months, that is January, February and March 2021. Based on three quality parameters, that is free fatty acids (FFA), water content and dirt content. The data is evaluated by the I-MR chart method and then compared with the quality specifications of the company and the buyer. Meanwhile, critical points and critical conditions that most influence the quality of palm oil were identified using the FMEA method. The results showed that FFA and water content of CPO were still not statistically controlled, which was indicated by the presence of data points that were outside the control limits. The parameter of FFA CPO quality in January 2021 is the highest with an average of 3.91%. The highest water content quality parameter is in March 2021 with an average 0.398%. And the highest dirt quality parameter was in February 2021 with an average 0.039%. The cause of the variation in the quality CPO was identified from 5 critical conditions where the highest RPN value is the use of restant fresh fruit bunch in the palm oil processing process. The proposed improvement that can be given to palm factory PT.XYZ is to implement a fast processing system using the FIFO (First In First Out) system so that the raw materials that is fresh fruit bunch are not too long and pile up at the loading ramp.